Relationship of Corporate Governance with Organizational Resilience in the Changing World - Melike Sercan Sevimli; Murat Çemberci (Journal of International Trade, Logistics and Law, 2021)
In addition to economical changes,technological improvemenets and crisis; occured company scandals like Enron and Worldcom has increased the interest in corporate governance concept. While corporate governance principles created by OECD in international context, in our country the principles created by SPK based on Anglo-Saxon corporate governance model. To encourage firms about adopting corporate governance and measure adoption level of firms who enrolled to stock markets to the codes in question, XKURY has been created by İstanbul Stock Market. When the effects of changes and developments in the fields of economy and technology on the management understanding and strategies of the enterprises considered, ability of the businesses that have adopted corporate governance principles to continue their activities in a healthy way, even if environmental factors become difficult or encounter any destructive events raises questions regarding to the relationahip between corporate governance and organizational resilience. This research has been made to understand if there is a correlation between corporate governance and organizational resilience. While data regarding to corporate governance point acquired as secondary sources via XKURY, data regarding to organizational resilience has been acquired as primary source via a survey that made up of organizational resilience scale created by Wicker et al. For dependent variable of the work, samples picked via snowball sampling method and collected data analyzed on the last word statistic softwares and Excel 2016. Analyze results showed that there is strong positive way correlation between corporate governance and organizational resilience.